BERTANI ITU KEREN: Efforts to increase agribusiness entrepreneurial intentions among youth - Elissa Dwi Lestari; Wim Prihanto; Nosica Rizkalla; Irwan Fakhruddin; Yearry Panji Setianto (Community Empowerment, 2024)
This community service activity in the form of an entrepreneurship seminar was carried out as one of the stages in strengthening the resilience of disaster-resilient communities in the South Lebak area. Based on the needs analysis with stakeholders, it was found that there was a problem with the interest of the younger generation in becoming farmers. The agricultural sector, which is the main contributor to the gross regional domestic product (GRDP) of Lebak Regency, has low sustainability because the young generation who are the successors of agricultural land are reluctant to become farmers and choose to work in the formal and informal sectors. The purpose of this community service is to foster a positive attitude towards agribusiness and foster entrepreneurial intentions among youth. The method used is to conduct an entrepreneurship seminar. Based on the seminar entitled "Farming is Cool", the youth in Panggarangan Village, South Lebak experienced an increase in positive perceptions about a career as a farmer. Furthermore, participants also stated that the entrepreneurship seminar conducted motivated them to work in agriculture.